PELATIHAN MEDIA AJAR MENGGUNAKAN QUIZIZZ DI PONDOK PESANTREN QADRATULLAH BANYUASIN - Fenny Purwani; Rusmala Santi; Gusmelia Testiana; Evi Fadilah; Imamulhakim Syahid Putra; Aminullah Imal Alfresi; Sri Rahayu; Muhammad Son Muarie; M Leandry Dalafranka; Gina Agiyani; Indah Hidayanti (Politeknik Negeri Sriwijaya, 2023)
Learning by conveying material or lectures is considered less effective and so monotonous in the teaching and learning process that has been carried out in each school, for this reason media support is needed in delivering the material to be studied so that students have an interest in learning. In addition, with this learning method, it is hoped that learning activities can be carried out properly and the quality and quantity of students will increase. Absorption of material presented by the author will be easier if done with an effective learning method. Therefore, on Tuesday 08 March 2022, from 09.00 to 12.00 the PKM team at Raden Fatah State Islamic University Palembang, consisting of 11 lecturers and 3 students, had the opportunity to provide training in coordination with the pesantren and 25 students. This training aims to provide knowledge and add insight to activity participants about the importance of using technology-based learning media. The importance of teaching media that is carried out makes students more interested in the learning system using quizziz. The result achieved by the participant were more enthusiastic in learning using this Quizizz learning media.